Designing Flexibility, Accessibility, and Independent Learning through the Use of Hyperapp Blended Learning Module - Mansur, Hamsi; Mastur; Monry Fraick Nicky Gillian Ratumbuysang; Fitria Yuniarti (Jurnal Komunikasi Pendidikan, 2024)
The quality of e-learning is determined by two factors, learning resources and the learning processes. However, sometimes the main factor behind the low quality of e-learning is the lack of teachers in creating the learning process. E-learning ranges from "adjunct" to "blended/hybrid" to "full online." Therefore, this research attempts to analyze the use of the hyperapp module for blended learning as a guide for teachers in designing flexibility, accessibility, and independent learning. The method used in this research is literature study. This hyperapp blended learning module provides clear and practical guidelines to teachers on integrating ICT, designing a rich learning experience, enhancing flexibility and accessibility of learning, and fostering students' self-directed learning. The research findings indicate that the conclusion drawn from this research is that the use of the hyperapp module equips teachers with good skills in designing blended learning, making the created learning flexible, accessible, and fostering independent learning. This conclusion is supported by various findings from previous research conducted by other researchers. The contribution of this research can provide insights that the use of the hyperapp module becomes more effective, relevant, and supportive of student development in this digital era.